Open tundra persist, but arctic features decline-Vegetation changes in the warming Fennoscandian tundra - Vuorinen, Katariina E M; Oksanen, Lauri; Oksanen, Tarja; Pyykönen, Anni; Olofsson, Johan; Virtanen, Risto (Global change biology, 2017)
In the forest-tundra ecotone of the North Fennoscandian inland, summer and winter temperatures have increased by two to three centigrades since 1965, which is expected to result in major vegetation changes. To document the expected expansion of woodlands and scrublands and its impact on the arctic vegetation, we repeated a vegetation transect study conducted in 1976 in the Darju, spanning from woodland to a summit, 200 m above the tree line. Contrary to our expectations, tree line movement was not detected, and there was no increase in willows or shrubby mountain birches, either. Nevertheless, the stability of tundra was apparent. Small-sized, poorly competing arctic species had declined, lichen cover had decreased, and vascular plants, especially evergreen ericoid dwarf shrubs, had gained ground. The novel climate seems to favour competitive clonal species and species thriving in closed vegetation, creating a community hostile for seedling establishment, but equally hostile for many arctic species, too. Preventing trees and shrubs from invading the tundra is thus not sufficient for conserving arctic biota in the changing climate. The only dependable cure is to stop the global warming.
Keywords: mosses; Arktida; Arctic Regions; stromy; reindeer; lichens; tundra; globální oteplování; climate change; alpine; Trees; vegetation; disturbance; Global Warming; Tundra; lesy; arctic; tree line; Empetrum nigrum; Forests